2013
DOI: 10.1002/asl2.410
|View full text |Cite
|
Sign up to set email alerts
|

Impact of freshening over the Southern Ocean on ENSO

Abstract: The response of El Niño-Southern Oscillation (ENSO) to idealized freshwater forcing over the Southern Ocean (SO) is investigated using a fully-coupled climate model. Modeling results explicitly show that freshening over the SO can modulate mean climate of tropical Pacific, triggering La Niña-like sea surface temperature (SST) anomalies and a sharper zonal tilt of tropical thermocline, which further influences ENSO variability. Amplitude of ENSO is intensified due to shallower thermocline in central-eastern tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…These studies have demonstrated that FWF and its related salinity fields first affect the oceanic density gradients and stratification, and then have the ability to maintain the mean climate and its variability (e.g., Maes, 2000;Lagerloef, 2002;Curry et al, 2003;Boyer et al, 2005;Levitus et al, 2005;Ballabrera-Poy et al, 2007;Cravatte et al, 2009;Collins et al, 2010). For instance, sensitivity analyses following an introduction of FWF perturbation have revealed obvious effects on SSTs (Levitus, 1989;Delcroix and Hénin, 1991;Manabe and Stouffer, 1995;Béthoux et al, 1998;Maes, 1998;Wong et al, 1999Wong et al, , 2001Dickson et al, 2002;Jacobs et al, 2002;Fedorov et al, 2004;Ma et al, 2013). In considering the coupling between the ocean and atmosphere, some additional processes start to act because the FWF forcing-induced changes in SSTs can produce additional feedback to the atmosphere.…”
Section: Introductionmentioning
confidence: 97%
“…These studies have demonstrated that FWF and its related salinity fields first affect the oceanic density gradients and stratification, and then have the ability to maintain the mean climate and its variability (e.g., Maes, 2000;Lagerloef, 2002;Curry et al, 2003;Boyer et al, 2005;Levitus et al, 2005;Ballabrera-Poy et al, 2007;Cravatte et al, 2009;Collins et al, 2010). For instance, sensitivity analyses following an introduction of FWF perturbation have revealed obvious effects on SSTs (Levitus, 1989;Delcroix and Hénin, 1991;Manabe and Stouffer, 1995;Béthoux et al, 1998;Maes, 1998;Wong et al, 1999Wong et al, , 2001Dickson et al, 2002;Jacobs et al, 2002;Fedorov et al, 2004;Ma et al, 2013). In considering the coupling between the ocean and atmosphere, some additional processes start to act because the FWF forcing-induced changes in SSTs can produce additional feedback to the atmosphere.…”
Section: Introductionmentioning
confidence: 97%
“…Today, it is poised at shallow depths. As a consequence, small changes in its depth through east-west tilting regulated by short-term climate phenomena such as the El Niño-Southern Oscillation can affect surface-water properties and ocean-atmosphere exchange processes (Fedorov et al, 2004;Ma et al, 2013). In general, proxy records and modeling results consistently document a long-term shoaling of the thermocline in the EEP and other (sub-)tropical upwelling regions throughout the Plio-Pleistocene (Wara et al, 2005;Fedorov et al, 2006;Steph et al, 2006aSteph et al, , 2010Dekens et al, 2007;Ford et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…Here we extend on previous work (e.g., Ma et al, 2013) by employing a state-of-the-science coupled climate model at relatively high spatial resolution and test a range of meltwater fluxes that are realistic in light of estimated past and future changes in the AIS. We focus specifically on the simulated changes at low latitudes resulting from the meltwater-induced changes in SH high-latitude surface conditions and the relationship between the magnitude of the meltwater-induced temperature anomalies and the resulting climatic change in the low latitudes.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the lack or highly simplified nature of atmospheric dynamics, the first two types of models do not allow to investigate the impact of Southern Ocean cooling on the ITCZ. The studies using coupled general circulation models did indeed find an impact of Southern Ocean cooling on low latitude climates (Ma & Wu, ) as well as changes in the characteristics of ENSO (Ma et al, ), but did not analyze the impact on the general atmospheric circulation in the tropics.…”
Section: Introductionmentioning
confidence: 99%